2021
DOI: 10.1136/bmjopen-2021-050045
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and neuropsychological outcomes in critically Ill patients with COVID-19: a cohort study

Abstract: ObjectiveTo characterise the clinical course of delirium for patients with COVID-19 in the intensive care unit, including postdischarge neuropsychological outcomes.DesignRetrospective chart review and prospective survey study.SettingIntensive care units, large academic tertiary-care centre (USA).ParticipantsPatients (n=148) with COVID-19 admitted to an intensive care unit at Michigan Medicine between 1 March 2020 and 31 May 2020 were eligible for inclusion.Primary and secondary outcome measuresDelirium was the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
4
21
3
1
Order By: Relevance
“…Supporting this concept, ∼70% of intensive care unit COVID-19 patients presented delirium symptoms that were likely connected to the underlying anti-cholinergic mechanisms [ 123 ], and associated with neuropsychological impairments. These symptoms lasted several months after discharge, based on data collected from a single-center cohort that supported previous findings of higher delirium incidence in critically ill patients with COVID-19 [ 126 ]. Further, COVID-19-induced delirium was correlated to the higher inflammatory response and 70% of COVID-19 patients with delirium were females [ 126 ].…”
Section: Future Prospects For Elucidating Post-covid Attention Defici...supporting
confidence: 85%
See 1 more Smart Citation
“…Supporting this concept, ∼70% of intensive care unit COVID-19 patients presented delirium symptoms that were likely connected to the underlying anti-cholinergic mechanisms [ 123 ], and associated with neuropsychological impairments. These symptoms lasted several months after discharge, based on data collected from a single-center cohort that supported previous findings of higher delirium incidence in critically ill patients with COVID-19 [ 126 ]. Further, COVID-19-induced delirium was correlated to the higher inflammatory response and 70% of COVID-19 patients with delirium were females [ 126 ].…”
Section: Future Prospects For Elucidating Post-covid Attention Defici...supporting
confidence: 85%
“…These symptoms lasted several months after discharge, based on data collected from a single-center cohort that supported previous findings of higher delirium incidence in critically ill patients with COVID-19 [ 126 ]. Further, COVID-19-induced delirium was correlated to the higher inflammatory response and 70% of COVID-19 patients with delirium were females [ 126 ]. This adds up to the consistent reports of increased risk of dementia in aged patients under long-term anticholinergic medications [ 88 ].…”
Section: Future Prospects For Elucidating Post-covid Attention Defici...supporting
confidence: 85%
“…Studies have found that 30% to 51.8% of critically ill COVID-19 patients had at least one episode of hyperactive delirium, which is substantially higher than the pre-pandemic incidence of 12.7% in critically ill patients [50,54,55]. The reason behind this high rate of agitation in COVID-19 patients is unclear; this could be related to the greater severity of COVID-19 lung injury and higher levels of ventilatory support, the frequent use of prone positioning, a relatively higher incidence of young individuals needing critical care during early COVID-19 surges, crisis staffing with providers less experienced in effective sedation management, decreased family visitation, or perhaps biological mechanisms unique to SARS-CoV-2 infection [50,[55][56][57][58].…”
Section: Epidemiology and Presentationmentioning
confidence: 99%
“…In critically ill patients, delirium is associated with a higher mortality independently from the severity of the main underlying disease and of the preexisting individual risk factors ( 12 ). Studies on large cohorts of ICUs patients have reported delirium to be highly prevalent and prolonged ( 15 ) with patients also showing persistent neuropsychological dysfunctions even after discharge ( 16 ). However, delirium is highly prevalent in mechanically ventilated patients ( 17 ), even though delirium rate in ICU seems to be declining in recent years ( 18 ).…”
Section: Introductionmentioning
confidence: 99%